Mining and heterologous expression of bacteriocins from Limosilactobacillus fermentum LBM97. (December 2021) - Gu, Yaxin; Ismael, Mohamedelfateh; Wang, Xin; Liu, Bianfang; Shan, Yuanyuan; Chen, Yujie; Zhou, Yuan; Yi, Yanglei; Lü, Xin
Abstract: Mass production of bacteriocin has always been an intractable problem in the food industry. To mine the bacteriocin with potential application produced by Limosilactobacillus fermentum LBM97, we collected the extracellular proteins of L.fermentum LBM97 for Label-free proteomic analysis and identified 41 putative bacteriocin-encoding genes. Five promising bacteriocins were heterologously expressed and their physical properties were investigated. Among them, LBM97-1, LBM97-4 and LBM97-5 showed antibacterial activity against Staphylococcus aure us ATCC25923 and LBM97-5 was also effective against Escherichia c oli ATCC25922. LBM97-5 has a good inhibitory effect on a variety of Gram-positive and Gram-negative pathogens. Furthermore, it has a good storage trait at 4 °C for more than 21 days, stable activity at wide ranges of temperature from 60 to 121 °C and pH from 2 to 10. In conclusion, Label-free proteomics is a powerful technique to mine bacteriocins from L.fermentum LBM97. Bacteriocin LBM97-5 with broad antimicrobial activity has great potential to be developed as a safe biopreservative in the food industry.